MENELAAH KESUSASTRAAN DAN KARYA SASTRA DINASTI ABBASIYAH - Nisa Meisa Zarawaki (Universitas Warmadewa, 2022)
Abbasiyah Dynasty encountered a fast development in several sectors, one of which is literature. Islamic literature shone brighter in the Abbasiyah era because the government and the whole society vastly appreciated Abbasiyah's literature works. Abbasiyah Literature experienced genre renewal, introducing more variety of genres. In prose and lyric works, there was an expansion in the purpose and theme of their written works. Literature characters who were popular in lyric and prose genre are Ibn Al-Muqaffa dan Abu Nuwas. The discussion of this journal is about the figurative language or language style used in Abbasiyah literature works, especially a lyric of Abu Nawas with the title of â€œal-Iâ€™tirafâ€ and prose of Ibn Al-Muqaffa with the title of â€œKalilah Wa Dimnahâ€. The method used is a stylistic method that is a method to analyze the language style or the figurative language in a work. The majority of Abu Nuwas dan Ibn Al-Muqaffa's language style is idiom and oxymoron. The characteristics of Abbasiyah literature work visible explicitly in its purpose in which to be the forerun of new genre emergence in Abbasiyah literature, i.e., novel, legend, and biography. Keywords: Abbasiyah; Abu Nawas; Ibn Al-Muqaffa; Language style; Lyric; Prose; Stylistic